1988
DOI: 10.1007/bf00203203
|View full text |Cite
|
Sign up to set email alerts
|

The pressure and temperature dependence of the elastic properties of single-crystal fayalite Fe2SiO4

Abstract: Abstract. The nine adiabatic elastic stiffness constants of synthetic single-crystal fayalite, FezSiO4, were measured as functions of pressure (range, 0 to 1.0 GPa) and temperature (range, 0 to 40 ~ C) using the pulse superposition ultrasonic method. Summary calculated results for a dense fayalite polycrystalline aggregate, based on the HS average of our single-crystal data, are as follows: Vp-6.67km/s; V~ = 3.39 km/s; K = 127.9 GPa; # = 50.3 GPa; (~K/SP)r = 5.2; (8 #/SP)r = 1.5;(~ K/~ T)e = --0.030 GPa/K; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 37 publications
8
42
2
Order By: Relevance
“…Figure 4 shows that sound wave velocities of Graham et al (1988) and Isaak et al (1993) are well represented by models G and I, respectively. Figure 4 also indicates that the transverse sound wave velocities given by Graham et al (1988) are not significantly different from that reported by Isaak et al (1993). The difference is significant for the longitudinal sound wave velocity.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Figure 4 shows that sound wave velocities of Graham et al (1988) and Isaak et al (1993) are well represented by models G and I, respectively. Figure 4 also indicates that the transverse sound wave velocities given by Graham et al (1988) are not significantly different from that reported by Isaak et al (1993). The difference is significant for the longitudinal sound wave velocity.…”
Section: Discussionmentioning
confidence: 93%
“…We used our method described by de Jong (2005a, 2007) as an inversion technique to conduct analyses of thermodynamic, vibrational and sound velocity data aiming at a consistent description of these properties. Because the adiabatic bulk modulus of fayalite measured by Graham et al (1988) and those by Isaak et al (1993) deviate from each other by about 10 GPa, we performed two analyses directing the optimization to either of these two datasets. Table 1 shows the result of two analyses obtained by a least-squares optimization process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations